Effects of Medical Diagnostic X-rays Delivered at 0.01 or 0.05 mGy on Human Blood Cells (Bangladesh Journal of Medical Science, 2021)
Background: Low-dose X-rays are commonly used in medical imaging to help in the diagnosis ofdiseases. However, the deleterious effects of exposure to medical diagnostic low-dose X-rays remaina highly debated topic. The objective was to study the effects of medical diagnostic X-rays on humanblood cells.Materials and Methods: We studied the effects of medical diagnostic low-dose X-rays (80kVp), i.e.,0.01 or 0.05 mGy, after the in vitro exposure of human red blood cells (RBCs) and peripheralblood mononucleated cells (PBMCs).Cells with no irradiation served as the control group. The biologicalendpoints that were used to determine the effects of medical diagnostic low-dose X-rays were hemolysisfor RBCs and mitochondrial membrane potential, lysosomes, and the cell cycle for PBMCs.Results: Ourresults showed no changes in the hemolysis of RBCs and mitochondrial membrane potential, lysosome, orcell cycle in cells exposed to these low doses of X-rays when compared to the corresponding nonirradiatedcells at all harvest timepoints.Conclusion: These results suggested that there were no deleterious effectsof diagnostic low-dose X-rays when human RBCs and PBMCs were exposed in vitro.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.136-144